Ectoparasitic Fauna of Scavenging Chickens (Gallus Domesticus) from Penang Island, Peninsular Malaysia - A. Rahman, Wahab; M.T., Farah Haziqah (Department of Veterinary Services Malaysia, 2015)
A study was conducted on 240 scavenging chickens randomly obtained from various districts from the state of Penang, Peninsular Malaysia. The chickens were closely examined for visible ectoparasites in the laboratory. The ectoparasites were collected using a blunt forceps and stored in universal bottles containing 70% ethanol. Ten species of ectoparasites were noted which consisted of fi ve species of lice, two species of mites, two species of ticks and one species of chigger. The lice identifi ed were Menopon gallinae, Menacanthus pallidulus, Lipeurus caponis, Goniocotes gallinae and Goniodes dissimilis. These lice occurred in the fl uff of the feathers of the body especially the neck, back, abdomen and wings. The mites were Megninia sp. and Pterolichus sp. Examinations of the ears and combs revealed Haemaphysalis sp., the hard tick. Meanwhile, Ornithonyssus sp., the soft tick was found on feathers, whereas chigger, Leptotrombidium sp. was found attached to the skins. The study also revealed that M. gallinae was the most common ectoparasite with 76.7% occurrence, followed by Pterolichus sp. (69.6%), L. caponis (63.3%), M. pallidulus (41.7%), Leptotrombidium sp. (17.5%), G. gallinae (9.5%), Haemaphysalis sp. (6.7%), Megninia sp. (3.8%) and Ornithonyssus sp. (3.8%). The least common ectoparasite was G. dissimilis occurring in 2.1% of the chickens